Anisotropy of magnetic susceptibility of earthquake-affected soft sediments: example from Ther village, Latur, Maharashtra, India. - Lakshmi, B.V.; Satyanarayana, K.V.V.; Basavaiah, N.; Gawali, P.B. (My University, 2015)
Anisotropy of magnetic susceptibility (AMS) of deformed and undeformed unconsolidated clay samples of Deccan Trap terrain from the ~2000-year-old palaeo-earthquake site of Ther village, Maharashtra, India, was studied. Such deposits are rare in this region and give an exceptional opportunity to test the efficacy of AMS and other magneto petrofabric studies, which can have a bearing on magnetic granularity ellipsoids, inclination and declination directions impacting palaeo-magnetic studies. The undeformed clay samples exhibit typical sedimentary fabric with an oblate AMS ellipsoid, whereas the deformed samples are tightly grouped in the inferred compression direction, probably effected by an earthquake, exhibiting prolate as well as oblate AMS ellipsoids. The temperature-dependent magnetic susceptibility revealed the occurrence of titanomagnetite and magnetite in both the deformed and undeformed samples signifying similar sediment material. The site mean ChRM direction for undeformed clay samples is D = 3 and I = 44.7 (k = 92.7, α95 = 4.5), whereas for deformed samples D = 336 and I = 39 (k = 39, α95 = 8). The present study reveals that sediments can be severely deformed without deflecting minimum susceptibility directions. AMS methodology can be effective in the DT region and can throw up new results to build the chronology of past earthquakes.
Keywords: Anisotropy of magnetic susceptibility; Characteristic remanent magnetization; Earthquake; Soft sediments; Latur; Maharashtra